Cardiac structure and function in schizophrenia: cardiac magnetic resonance imaging study. (August 2020) - Osimo, Emanuele F.; Brugger, Stefan P.; de Marvao, Antonio; Pillinger, Toby; Whitehurst, Thomas; Statton, Ben; Quinlan, Marina; Berry, Alaine; Cook, Stuart A.; O'Regan, Declan P.; Howes, Oliver D.
Abstract : Background: Heart disease is the leading cause of death in schizophrenia. However, there has been little research directly examining cardiac function in schizophrenia. Aims: To investigate cardiac structure and function in individuals with schizophrenia using cardiac magnetic resonance imaging (CMR) after excluding medical and metabolic comorbidity. Method: In total, 80 participants underwent CMR to determine biventricular volumes and function and measures of blood pressure, physical activity and glycated haemoglobin levels. Individuals with schizophrenia ('patients') and controls were matched for age, gender, ethnicity and body surface area. Results: Patients had significantly smaller indexed left ventricular (LV) end-diastolic volume (effect size d = −0.82, P = 0.001), LV end-systolic volume ( d = −0.58, P = 0.02), LV stroke volume ( d = −0.85, P = 0.001), right ventricular (RV) end-diastolic volume ( d = −0.79, P = 0.002), RV end-systolic volume ( d = −0.58, P = 0.02), and RV stroke volume ( d = −0.87, P = 0.001) but unaltered ejection fractions relative to controls. LV concentricity ( d = 0.73, P = 0.003) and septal thickness ( d = 1.13, P < 0.001) were significantly larger in the patients. Mean concentricity in patients was above the reference range. The findings were largely unchanged after adjusting for smoking and/or exercise levels and were independent of medication dose and duration. Conclusions: Individuals with schizophrenia show evidence of concentric cardiac remodelling compared with healthy controls of a similar age, gender, ethnicity, body surface area and blood pressure, and independent of smoking and activity levels. This could be contributing to the excess cardiovascular mortality observed in schizophrenia. Future studies should investigate the contribution of antipsychotic medication to these changes.